Capital Adequacy Ratio and Financial Performance of Commercial Banks in Nepal - Bhattarai, Dhundi Raj (Tribhuvan University Journal, 2021)
The Purpose of this study is to measure the impact of capital adequacy ratio i.e., core capital ratio, supplementary capital ratio, and total capital fund ratio; financial performance i.e., return on assets and return on equity as well as their relationship. It has also focused on effect of capital adequacy ratio on financial performance of commercial banks in Nepal. Descriptive and casual comparative research design has been used in this study. It is based on secondary sources of data. The data were collected from annual audit report of twenty-six commercial banks from fiscal year 2012/13 to 2018/19 out of twenty-seven. Rastriya Banijya Bank has been excluded in this study due to the unavailability of annual audit report. Total number of observations were 182. The mean range, standard deviation, coefficient of variation, correlation analysis, and regression analysis statistical tools were used in this study. This study reveals that the return on equity is highly scattered in comparison to return on equity. Supplementary capital is highly spread in comparison to core capital ratio. There is low degree of positive relationship of return on assets with core capital ratio and supplementary capital ratio. There is low degree of positive relationship of return on equity and supplementary capital however low degree of inverse relationship in between return on equity and core capital. Core capital ratio and total capital fund ratio positively influence on return on assets and return on equity.